2018
DOI: 10.1111/ijpo.12488
|View full text |Cite
|
Sign up to set email alerts
|

Sugary, fatty, and prominent: food and beverage appearances in children's movies from 1991 to 2015

Abstract: Summary Background Media presentations of unhealthy food are considered a contributor to childhood obesity. Objective This study describes food and beverage presentations in a longitudinal sample of children's movies. Methods We conducted a content analysis of the 250 most successful children's movies from 1991 to 2015. We identified and coded food and beverage appearances and differentiated between healthy, mixed, and unhealthy products. We also coded integration characteristics and movie characteristics. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 28 publications
(67 reference statements)
3
50
0
2
Order By: Relevance
“…A possible theoretical explanation for this phenomenon could be priming theory . As children are so used to being confronted with unhealthy foods, this information might be easier for them to retrieve from memory. This of course has important implications for children's food choices that are connected to their accessible food categories .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible theoretical explanation for this phenomenon could be priming theory . As children are so used to being confronted with unhealthy foods, this information might be easier for them to retrieve from memory. This of course has important implications for children's food choices that are connected to their accessible food categories .…”
Section: Discussionmentioning
confidence: 99%
“…However, what kind of food is presented in the media is often far off the ideal reality of a balanced, and healthy diet . Content analyses on food presentations in commercials and entertaining media unequivocally suggest that unhealthy foods high in salt, fat or/and sugar are overrepresented compared to healthy foods . Effect studies on unhealthy food placements, such as salty snacks, sweets and soft drinks, have furthermore continuously shown that children's attitudes and consumption behaviors are heavily influenced by these presentations .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that low nutritional value foods were more prominent than high nutritional value foods when it comes to animated cartoons targeted to audiences over age 7. Similarly, in Matthes and Naderer (2018) [4]'s content analysis of foods placed in children's movies which also measured placement interaction and placement consumption, higher persuasive potential of low nutritional value food placements compared to high nutritional value food placements was found. According to SCT [35], both the salience (prominence) and the context (positive, neutral and negative) of messages placed in media influence modelled behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…To date, most of the studies about food placements directed at children have focused on branded foods [7,[9][10][11]. While branded food placements are frequent in movies [4] and advergames [3] targeting children, non-branded food placements are the type of products found in cartoons [5], as branded food placements are prohibited in these animated series [16]. This prohibition aims to protect infants against the persuasive effects of branded product placements as children constitute a vulnerable target group [17].…”
mentioning
confidence: 99%